Application of Feed Supplements to Improve the Growth Performance of White Shrimp Litopenaeus vannamei with Clinical Symptoms of AHPND Disease - Hanggit Damarjati Albar; Ima Kusumanti; Luqman Hakim; Wiyoto Wiyoto (College of Vocational Studies, Bogor Agricultural University, 2025)
White shrimp Litopenaeus vannamei is a type of shrimp that has high economic value and is included in indonesias fisheries export commodities. The high market demand makes farmers continue to strive to increase production, however, efforts to increase its production are often faced with various problems, such as attacks by Acute Hepatopancreatic Disease (AHPND). Clinical symptoms resulting from the disease are damage to digestive organs, stunted shrimp growth, and mass death. Efforts that can be made to increase the appetit and growth of vaname shrimp can be done by applying feed supplement, combination of Boster Amino Liquid, Premix Aquavita, and Grotop with oral method by mixing them with feed. This activity aims to determine to evaluate feed supplement application on the growth and survival rate of white shrimp and compare the result of two different growing media (soil pond and HDPE plastic pond). The result obtained showed an increase in shrimp growth and survival rate (SR), with the value of SR in soil pond is 26,9% which lower compared to HDPE plastic pond (70,6%). Changes in weather and water quality in cultivation ponds are the crucial factor affecting the result.